Mefunidone ameliorates renal inflammation and tubulointerstitial fibrosis via suppression of IKKβ phosphorylation. (November 2016) - Zhang, Jin; Zheng, Linfeng; Yuan, Xiangning; Liu, Chunyan; Yuan, Qiongjing; Xie, Feifei; Qiu, Sisi; Peng, Zhangzhe; Tang, Yiting; Meng, Jie; Qin, Jiao; Hu, Gaoyun; et al.
Abstract: Mefunidone is a new pyridone agent that attenuates renal tubulointerstitial fibrosis. However, the signaling pathways involved in the effect of mefunidone on renal tubulointerstitial fibrosis have not been well explained. Inflammatory response initiates and promotes renal tubulointerstitial fibrosis, and the inhibitor of nuclear factor kappa-B kinase beta (IKKβ) is a master regulator of inflammation. This study is determined to clarify the influence of mefunidone on renal inflammation and the phosphorylation of IKKβ. Experimental renal tubulointerstitial fibrosis was induced by unilateral ureteral obstruction (UUO) for 3, 7 and 14 days in sprague dawley rat. Treatment with mefunidone was conducted simultaneously. Obstructed kidneys were harvested for the assessment. Our results showed that treatment with mefunidone ameliorated renal inflammatory injury, renal tubular lesions and interstitial fibrosis. Further studies indicated that treatment with mefunidone mitigated the expressions of tumor necrosis factorα (TNFα) and interleukin-1β (IL-1β) in the kidney. The phosphorylation of IKKβ and inhibitor of kappa-B (IκB) and the expression of NOD-like receptor family, pyrin domain containing 3 (NALP3) were also reduced in vivo after treatment with mefunidone. In vitro, peritoneal macrophages were incubated with necrotic cells or lipopolysaccharide in the presence or absence of mefunidone. Mefunidone markedly decreased necrotic cell or LPS induced IL-1β production and LPS induced TNFα production in primary peritoneal macrophages. Furthermore, mefunidone significantly inhibited the phosphorylation of IKKβ/IκB and nuclear transition of NF-κB p65 in peritoneal macrophages stimulated by necrotic cell or lipopolysaccharide. In conclusion, mefunidone serves as a novel anti-inflammatory agent that attenuates UUO-induced renal interstitial inflammation and fibrosis, possibly through suppressing IKKβ phosphorylation.